Bank Capital Regulation in a Model of Modern Banking Crises - Xue Zhang; Johannes Poeschl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study the macroeconomic effects of retail bank capital regulation in an economy with a retail and a shadow banking sector. The financial instability takes the form of bank runs on the shadow banking sector. Retail bank capital regulation reduces the frequency of bank runs by mitigating the drops in capital price during fire sales. The aggregate capital stock decreases as a result of capital misallocation. The cost of bank capital requirement outweighs its benefit of fewer bank runs.
Keywords: E44; 330